2019
DOI: 10.1002/2211-5463.12757
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific effects of leptin administration to pregnant mice on the placentae and the metabolic phenotypes of offspring

Abstract: Obesity during pregnancy has been shown to increase the risk of metabolic diseases in the offspring. However, the factors within the maternal milieu which affect offspring phenotypes and the underlying mechanisms remain unknown. The adipocyte hormone leptin plays a key role in regulating energy homeostasis and is known to participate in sex‐specific developmental programming. To examine the action of leptin on fetal growth, placental gene expression and postnatal offspring metabolism, we injected C57BL mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…Inf luence of leptin administration to pregnant mice on liver weight and blood biochemistry in male and female offspring fed on the obesogenic diet Earlier we found that a single leptin administration to mice on pregnancy day 12 exerts sex-specific programming action on metabolism in the offspring (Denisova et al, 2020). Thus, females are sensitive to leptin in this period, as evident from lower food consumption in response to leptin.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Inf luence of leptin administration to pregnant mice on liver weight and blood biochemistry in male and female offspring fed on the obesogenic diet Earlier we found that a single leptin administration to mice on pregnancy day 12 exerts sex-specific programming action on metabolism in the offspring (Denisova et al, 2020). Thus, females are sensitive to leptin in this period, as evident from lower food consumption in response to leptin.…”
Section: Discussionmentioning
confidence: 91%
“…Leptin, a hormone produced in the adipose tissue, is considered to be a programming factor of the maternal environment. Model experiments indicate that high maternal leptin levels in the pregnancy reduce body weight, increase insulin sensitivity, and improve metabolic characteristics in the adult offspring fed on balanced or high-calorie diets, and this effect may manifest differently in different sexes (Pennington et al, 2012;Makarova et al, 2013;Pollok et al, 2015;Talton et al, 2016;Denisova et al, 2020). Nevertheless, molecular mechanisms mediating the programming action of maternal leptin remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, the placenta develops at a relative faster rate in males compared to females [ 13 ]. Relationships between fetal sex and placental functions have been demonstrated in many studies [ 14 , 15 , 16 , 17 , 18 , 19 ]. Recent study shows that uterine Foxa2 influences the growth of fetus and placenta in a sexual dimorphic manner [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However through the placental expression of adiponectin receptors, maternal adiponectin might limit fetal growth by inhibiting the production of placental lactogen, chorion gonadotropin and progesterone in trophoblast cells 52,53 . Both of these hormones have been linked to gestational diseases like preeclampsia [54][55][56][57][58] , gestational diabetes [58][59][60][61] and fetal outcomes like intrauterine growth restriction 46,58,59,[62][63][64][65][66] . While earlier work did find positive associations between placental leptin expression and birthweight 59,60,67 , several studies since have found a negative correlation -which is in line with our findings 63,65,[68][69][70][71][72] .…”
Section: Discussionmentioning
confidence: 99%